Effects of emotional response on the Stroop‐like task in preschool children and young adults1. (25th February 2014) - Ikeda, Yoshifumi; Okuzumi, Hideyuki; Kokubun, Mitsuru
Abstract This study investigated the effects of emotional response on an inhibitory task, the Stroop‐like day‐night task, in which participants are presented with two pictures. They are then requested to inhibit naming what the card shown to them represents and instead state what the other card represents. Specifically, 35 4‐ to 6‐year‐old children and 15 young adults were administered the emotion‐related happy‐sad task and the emotion‐unrelated up‐down task using the same stimulus set (happy and sad cartoon faces). The results suggested that vulnerability to errors in the happy‐sad task was not derived from increased inhibitory demand. The results also suggested that the happy‐sad task is more inhibitory‐demanding in terms of response time. These results suggested that the happy‐sad task elicits interference more than other variants of this task, not because the task involves emotional stimuli per se but because the task involves both emotional stimuli and emotional responses.